Prevalence of Anxiety and Depression Among the General Population in Africa During the COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Bello, Umar Muhammad; Kannan, Priya; Chutiyami, Muhammad; Salihu, Dauda; Cheong, Allen M. Y.; Miller, Tiev; Pun, Joe Wing; Muhammad, Abdullahi Salisu; Mahmud, Fatima Ado; Jalo, Hussaina Abubakar; Ali, Mohammed Usman; Kolo, Mustapha Adam; et al. (Frontiers in Public Health, 2022)
Background Medical and socio-economic uncertainties surrounding the COVID-19 pandemic have had a substantial impact on mental health. This study aimed to systematically review the existing literature reporting the prevalence of anxiety and depression among the general populace in Africa during the COVID-19 pandemic and examine associated risk factors. Methods A systematic search of the following databases African Journal Online, CINAHL, PubMed, Scopus, and Web of Science was conducted from database inception until 30th September 2021. Studies reporting the prevalence of anxiety and/or depression among the general populace in African settings were considered for inclusion. The methodological quality of included studies was assessed using the Agency for Healthcare Research and Quality (AHRQ). Meta-analyses on prevalence rates were conducted using Comprehensive Meta-analysis software. Results Seventy-eight primary studies (62,380 participants) were identified from 2,325 studies via electronic and manual searches. Pooled prevalence rates for anxiety (47%, 95% CI: 40–54%, I2 = 99.19%) and depression (48%, 95% CI: 39–57%, I2 = 99.45%) were reported across Africa during the COVID-19 pandemic. Sex (female) and history of existing medical/chronic conditions were identified as major risk factors for anxiety and depression. Conclusions The evidence put forth in this synthesis demonstrates the substantial impact of the pandemic on the pervasiveness of these psychological symptoms among the general population. Governments and stakeholders across continental Africa should therefore prioritize the allocation of available resources to institute educational programs and other intervention strategies for preventing and ameliorating universal distress and promoting psychological wellbeing. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021228023, PROSPERO CRD42021228023.